Uncommon Sense for Parents with Teenagers - Michael Riera (California Celestial Arts, 1995)
This question-and-answer book helps parents understand and cope with issues of modern teenage life: alcohol, drugs, and parties; academics; sex; eating disorders; homosexuality; divorce and remarriage - while encouraging parents to move from being their child's manager to being their consultant. The author's upbeat, unpatronizing approach to teenagers promotes true communication and understanding between parents and teens.
Keywords: Counselor -- Counselor